2019
DOI: 10.1038/s41598-019-55456-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilic risk factors for retinal vein occlusion

Abstract: The aim is to study risk factors for retinal vein occlusion (RVO), such as thrombophilic and cardiovascular risk factors (CRF). A retrospective consecutive case series of 60 patients with RVO was made, tested for CRF, hyperhomocysteinemia, lupic anticoagulant, antiphospholipid antibody and 5 gene variants: factor V (FV) Leiden (G1691A), factor II (PT G20210A), 5,1-methylenetetra-hydrofolate reductase (MTHFR; 677 C > T and 1298 A > C), plasminogen activator inhibitor 1 (PAI-1; 4 G/5 G). More than 1 CRF were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…As a parallel, the increased levels of prothrombin fragment, thrombinantithrombin complex, and plasma homocysteine were also reported as risk factors for RVO. [33][34][35] Moreover, hemodialysis is another risk factor for procoagulant and inflammatory effects in ESRD patients. 36 Our study showed the prevalence of CKD is higher in CRVO subgroup than BRVO subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…As a parallel, the increased levels of prothrombin fragment, thrombinantithrombin complex, and plasma homocysteine were also reported as risk factors for RVO. [33][34][35] Moreover, hemodialysis is another risk factor for procoagulant and inflammatory effects in ESRD patients. 36 Our study showed the prevalence of CKD is higher in CRVO subgroup than BRVO subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygosity of the mutated allele results in greater severity hyperhomocysteinemia than heterozygosity. [3] Hyperhomocysteinemia potentially caused the macular edema in our patient through two mechanisms. Firstly, indirectly, by causing elevation of venous and capillary pressure, stagnation of the blood flow (venous stasis) and subsequent hypoxia of the retina drained by the obstructed vein, damage to the capillaries and extravasations of blood elements [2].…”
Section: Discussionmentioning
confidence: 84%
“…Mild to moderate increase of homocysteine plasma levels is a reported risk factor for atherosclerosis in the coronary, cerebral, and retinal vasculature [ 2 ]. This disorder may be due to an acquired nutritional deficiency in vitamin cofactors (folic acid, vitamins B6 and B12), or a chronic medical condition, or an adverse drug effect [ 2 , 3 ]. Hyperhomocysteinemia is more frequently discovered in patients with RVO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vieira et al in their retrospective case series of 60 patients, suggested that “more than the relative prevalence of polymorphisms found in RVO, it is the association of MTHFR polymorphisms and younger age at diagnosis that may be more relevant.” 34 However, a study conducted by Larsson et al did not find any difference in either the prevalence of the mutation or hyperhomocysteinemia between controls and patients with CRVO, even if all patients over 50 were excluded 35 and Cruciani et al also failed to demonstrate that these mutation is a risk factor for RVO in patients under 50 years of age. 36 In a study by Biancardi et al the same frequency of MTHFR TT was found in cases and controls and this mutation did not represent a risk for RVO in patients younger than 60 years.…”
Section: Mthfr C677tmentioning
confidence: 95%